Aplikasi Layanan Pengaduan Kerusakan Jalan (APZARD) - Immanuel, Candra Great; Putro, Dimas Nugroho; Varadinta, Salsabilla; Siswanto, Joko (Proceedings Series on Physical & Formal Sciences, 2023)
Many roads suffer potentially harmful damage to road users. The slow pace of road repair and limited surveillance are constraints to create a road that is safe for the user. The APZARD application is a service of road damage between people and governments so that a faulty road can be found and repaired quickly. The research method used is the waterfall method with the steps of analysis, design, code and test. Results from the study indicate that the application could be run and used by the public to file road damage received by admin and then proceed to road repair. The APZARD application helps the government watch over the damaged roads and follows up complaints from road related damages.